PENGEMBANGAN MODEL PELATIHAN INNOMATTS UNTUK MENINGKATKAN KOMPETENSI DAN KARAKTER GURU MATEMATIKA - Mohammad Asikin; Iwan Junaedi; Adi Nur Cahyono (Universitas Negeri Semarang, 2015)
This research is a development research which aims to develop a training model which is able to improve mathematics teachers’ competence and character. This research was implemented into two year phase. The first year focused on the exploration study and the model validation. This phase successfully identified the need of the mathematics teachers and generated a valid training model called the Innovative Mathematics Teaching Study (INNOMATTS). The second year focused on the implementation and dissemination of the model. This article aims to describe the practicality and the effectiveness of INNOMATTS training model in improving mathematics teachers’ competence and character as it was developed based on the mathematics teachers’ need, containing mathematics learning innovation and having orientation toward character education. The research follows the Research and Development (R D) of Gall. The evaluation of the model implementation quality used three criteria: validity, practicality, and effectiveness. The result suggests that the INNOMATTS training model is practical based on the percentage response of the planning, implementation and evaluation. The model is also effective based on the evaluation of lesson plan produced during the training, the learning implemented, and the result of teacher’s competence test.